Differences in salivary flow rate and pH between chewing gum of xylitol and sucrose in elementary school students in Makassar - Sherly Horax; Sarah Eva Chalid; Eri Hendra Jubhari (Makassar Dental Journal, 2020)
Caries can be caused by various factors such as the amount of salivary flow, salivary acidity, etc. It needs to be known by chewing gum with xylitol and sucrose are most excellent to preventing caries in children. This study aimed to determine the difference of salivary flow while chewing xylitol gum and sucrose bubble gum in students of SD Inpres Toddopuli Makassar. This qualitative research with quase experimental studies method is the pre- and post-test design with control group. The sample criteria were children aged 9-12 years, has a superficial and media dental caries at least three teeth, did not another chewing gum about 60 minutes before examination, and willing to be research samples. As many as 30 samples each in grades 4, 5, and 6 chew xylitol gum on the first day and chew sucrose gum on the secong day of 5 minutes each. Saliva was collected on a cen-trifuge tube, observed amount and acidity of saliva. The results showed significants difference in the amount of salivary flow and acidity between xylitol chewing gum and sucrose chewing gum, namely there was different in amount of salivary flow (0.002) and for salivary pH value (0.000). It was concluded that children who chewed xylitol gum produce more saliva than sucrose chewed gum and sucrose gum had higher acidity than xylitol gum.